Analysis and application of sleeved column considering the extension of the inner core. (October 2021) - Zhao, X.F.; Tan, P.; Ma, H.T.; Zhou, F.L.; Shen, B.
Abstract: Instability of structural members under axial compression probably leads to collapses of space grid structures. Therefore, a sleeved column has been to improve the stability of the axially compressed member. This paper presented a theoretical investigation of the behavior of the sleeved column considering the extension of the inner core, focusing on the deformation process of point contact and line contact between the inner core and the sleeve. Equilibrium differential equations were established for the cases when in the state of point contact and line contact, and the expressions were derived for responses such as deflection, shearing force, bending moment and contact force of the sleeved column. The two models considering the extension of the inner core could accurately predict the mechanical properties of the sleeved column. The most important factor on the end of the sleeved column was the length of the extension of the inner core with the parametric analysis. Empirical formulas of the force at the end of the sleeved column were obtained through regression analysis, providing a basis for the design of the end part of the sleeved column. Highlights: A mechanical model of sleeved column considering the extension of core material is presented. The most important factor on the force of the sleeved column is the length of the extension of the inner core through verification and analysis. The mechanical properties of the sleeved column are obtained. Empirical calculation formulas of the force at the end of the sleeved column can provide a corresponding basis for the design of the end part of the sleeved column.